Ebüssuûd Efendi’nin Bidâ‘Atü’l-Kâdî adlı risalesinin tahkik ve tahlili - Balcı, Ahmet Ali (My University, 2016)
Ebüssuûd Efendi (ö.982/ 1574), Kanuni Sultan Süleyman ve II. Selim devirlerinde, devletin muhtelif kademelerinde altmış yıl kadar vazife yapmıştır. En önemlisi de otuz yıla yakın şeyhülislamlık yapmış olmasıdır. Kazaskerlik ve şeyhülislâmlık vazifeleri sırasında ilmiye ve devlet teşkilatını geliştirmeye çalışmış, dolayısıyla Osmanlı idari ve hukuki yapısına ciddi katkı sağlamıştır. Resmi vazifelerini ifa ederken muhtelif sahalarda eserler kaleme almıştır. Bu eserlerin çoğu, elyazması halinde bulunmaktadır. Araştırma konusu yaptığımız ve yine mahtut halde bulunan “Bidâ‘atü’l-kâdî li'htiyâcihi ileyhi fi’l-müstakbel ve’l-mâzî” isimli eseri, sakk mecmualarının ilki olma özelliğini taşımaktadır. Bu çalışmada, fazla hacimli olmaması hasebiyle risalenine tamamı tahkik edildi. Müellifin hayatı, talebeleri ve eserleri hakkında bilgi verildi. Bu çalışmada müellif nüshasına ulaşılamadığı için, ona en yakın metni ortaya koyabilmek amacıyla ulaşılabilen nüshalar içerisinden bazı kıstaslara göre üç tanesi tahkik için esas alındı. Nüshalar mukayese edilerek farklılıkları dipnotta gösterildi. Metin içerisinde geçen yabancı kelimelerin izahı ve ayetlerin numara ve sureleri dipnotta gösterildi. ssuûd Efendi, Şeyhülislâm, Bidâ’atü’l-Kâdî, Sakk, Osmanlı Hukuk Sistemi.

Ebussuud Efendi (d. 982/ 1574) served in several positions for approximately 60 years during the reigns of Sultan Suleiman the Magnificent and Sultan Selim II. More importantly, he worked as a shaykh al-Islam (grand mufti) for almost 30 years. While in the positions of kazasker and shaykh al-Islam, he tried to improve the ilmiyye and state structures, hence he made a considerable contribution to the Ottoman administrative and legal structures. While carrying out his official duties, he penned many works in varying fields. Unfortunately, most of these works are in the form of manuscript. This thesis considers Bida‘at al-Qadi li Ihtiyajih ilayh fi al-mustaqbal wa al-mazi, one of his works in the form of manuscript, which holds the distinction of being the first saqq (collection of law cases). Since this manuscript is not voluminous, a complete critical edition was constructed for this manuscipt. In addition, the information regarding author's biography, students and works was provided. In this study, since we could not obtain the manuscript written by the author himself, three manuscripts were, based on some objectives, chosen out of the manuscripts we have in order to construct a critical edition very close to the original manuscript. The selected manuscripts were compared and the differences among them were shown as footnotes. Furthermore, the explanations for the foreign words and surah (chapter) and ayat (verse) numbers were given in footnote. ssuûd Efendi, Shaykh al-Islam, Bida’at al-Qadi, Saqq, Ottoman Law
Keywords: Hukuk; İslam dini; İslam hukuku